Influence of organic manures on the growth of diabetes preventive medicinal plant Gynura, Gynura procumbens - Akon, MOS; Datta, DK; Biswas, T; Nakamura, K; Rahman, MK (Journal of Biodiversity Conservation and Bioresource Management, 2018)
A pot experiment was carried out to evaluate the effects of various organic manures on the growth performance and biomass production of Gynura procumbens in the net house of the Department of Soil, Water and Environment, University of Dhaka. Seven types of manures, viz. ACI, BGF-1, Mazim, Vermicompost, Sufola, GTS and Poultry litter composts were used separately at the rate of 15 ton/ha. Highest height (78cm) in poultry litter compost, leaf number (208.33 no./plant) in sufola manure, leaf area (53.64 cm2/plant) in vermicompost, and branch (3.67 no./plant), girth (3.07cm/plant), fresh weight (202.28g/plant) and dry weight (22.44g/plant) were recorded in poultry litter compost treatment at harvest. Height, leaf area, and fresh and dry weights of leaf varied significantly (p≤ 0.5) and increased with time. Results showed that the overall best growth performance was achieved in poultry litter compost. J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(2): 61-66